Examining the critical success factors of climate-inclusive financing for durable solutions in conflict-affected Baidoa city, Somalia - Mohamed Ibrahim Nor; Abdulkadir Mohamed Moge (Cogent Business & Management, 2024)
This study explores the critical factors of climate-inclusive financing for durable solutions for forcibly displaced persons (DSFS) in Baidoa, Somalia, focusing on the interplay between financial autonomy, governance, and spatial dynamics. Utilizing multiple regression analysis, the research integrates various predictors into a cohesive model, based on survey data from 66 experts in city governance, financial autonomy, and spatial factors. The study finds that limited financial independence (FICA) hinders DSFS success, while proactive city-level interventions positively influence outcomes. Interaction effects show that FICA combined with other factors can enhance intervention success. The spatial distribution of forcibly displaced persons (FDPs) negatively impacts policy implementation. Enhancing city authorities' financial autonomy could improve DSFS success. Policymakers should target strategic interventions that address FDP needs, consider urban spatial challenges, and incorporate climate-inclusive financing models. This study offers novel insights into the roles of financial autonomy and spatial dynamics in DSFS, contributing to urban planning and governance in fragile contexts. The research adds to the literature on urban displacement, governance, and climate finance, highlighting the key factors influencing DSFS.
Keywords: 650; Forcibly displaced persons; financial independence; city authority; urban planning; spatial distribution